2012
DOI: 10.1016/j.jcma.2012.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Citrus reticulata peel improves patient tolerance of low-volume polyethylene glycol for colonoscopy preparation

Abstract: Compared with conventional colonic preparation, the application of CRP as an adjunct could improve examinees' tolerance, decrease the incidence of adverse events, and maintain the quality of colonic cleansing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…The proportion of patients willing to undergo repeat bowel preparation in future was reported in five studies (Figure 2(c)), of which four ascertained outcomes prior to colonoscopy 6–8 , 10 . This outcome was significantly higher (OR 2.92, 95% CI: 1.97–4.35, p < 0.001) in the adjunct group (84.9%) vs control group (61.9%).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The proportion of patients willing to undergo repeat bowel preparation in future was reported in five studies (Figure 2(c)), of which four ascertained outcomes prior to colonoscopy 6–8 , 10 . This outcome was significantly higher (OR 2.92, 95% CI: 1.97–4.35, p < 0.001) in the adjunct group (84.9%) vs control group (61.9%).…”
Section: Resultsmentioning
confidence: 96%
“…[5][6][7][8][9][10] All of these were randomised controlled trials (RCTs), conducted between 2012-2016, which analysed the impact of adjuncts on the tolerability and quality of PEG-based bowel preparation. Adjuncts comprised citrus reticulata peel, 6 orange juice, 7 menthol candy drops, 8 simethicone, 5 Coke Zero 9 and sugar-free chewing gum. 10 Only one study 9 compared different solvents whilst the rest used adjuncts in addition to standard bowel preparation regimens.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known in China for thousands of years that medicine and food are derived from the same source, and their difference is just based on the individual health conditions (Zhao et al , ). CRP as an edible TCM is extensively applied all over the world because of its industrial value, mainly in foods and beverages (Lan et al , ). Phytochemical studies showed that abundant components are present in CRP, such as flavonoids, alkaloids, phenolic acids and essential oils, among which flavonoids were considered to be the primary bioactive components (Zheng et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…In the current issue of Journal of the Chinese Medical Association, Lan et al conducted an open trial to evaluate the beneficial effect of adding Citrus reticulata peel (CRP) as an adjuvant to low-volume PEG for colonoscopy preparation. 7 In traditional Chinese medicine, chen pi (the dried CRP) has been widely used for centuries as a remedy to treat indigestion (fullness, nausea, and vomiting). 8 The peel is aromatic and pungent in taste, and C. reticulata has been demonstrated to improve gastrointestinal motility in animal models of both in vivo and in vitro tests.…”
mentioning
confidence: 99%